Econometric estimation of the demand for meat in Namibia - Andjamba, Hiltrudis N. (University of the Free State, 2017)
This study estimated the Rotterdam and the LA/AIDS model with the reason to determine an appropriate model for Namibian meat products. The data used in the study are prices and quantity demanded for Namibian meat products, such as beef, mutton, pork and chicken, for the period from January 2001 to December 2013. The data were analysed using Eview 7 by Seemingly Unrelated Regression Estimation (RSURE) method that produces four separate equations, namely beef, mutton, pork and chicken equations. The data used in predicting both models were first tested to determine whether they are stationary. As a result, the data employed were integrated of order one (I(1)). The parameters of the models were estimated using the RSURE method. The econometric restrictions, such as homogeneity and asymmetry, were imposed during the estimation of both the models. Because the mutton equation was dropped during the regression process, the adding-up restriction was used to recover the parameters for the mutton in both the models. As for the Rotterdam model, the system R2 for the Rotterdam modes is 19.1 per cent. All expenditure coefficients are positive, which is in line with the a priori expectations. With the exception of chicken, the expenditure coefficients for beef (0.007), pork (0.014 and mutton (0.027) are very close to zero, implying that these products are normal goods. The beef share equation further indicates that an increase in the price of chicken (-0.004), pork (-0.003) and mutton (-0.007) reduces their share in the budget because consumers prefer to spend their income on beef. Unlike the Rotterdam model, all three sets of restrictions in the LA/AIDS model were satisfied during the regression. Nine out of twelve estimated parameters are statistically significant at one per cent level of confidence. One is significant at ten per cent level of significance, while only two parameters are insignificant. The system R2 (39.4) for the LA/AIDS model is higher than that of the Rotterdam model. The estimated expenditure elasticities for beef, chicken, pork and mutton are 0.60, 1.46, 0.41 and 1.06, respectively. Beef and pork are relatively inelastic, while chicken is more elastic than mutton is. The expenditure elasticity result for the LA/AIDS model implies that chicken and mutton are regarded as luxury products, while beef and pork are normal goods in the Namibian purchasing basket. Based on the performance of the two models on Namibian meat data, the LA/AIDS model, compared with the Rotterdam model, performed better in terms of the model’s ability to meet the econometric restrictions of homogeneity and asymmetry, the highest adjusted R2, and the results that are in conformity with the a priori expectation in terms of compensated own-price and cross-price elasticities. It is therefore concluded that the LA/AIDS models are a better fit for the Namibian meat data.
Dissertation (M.Sc.Agric. (Agricultural Economics))--University of the Free State, 2017
Keywords: Livestock -- Economic aspects; Meat industry and trade -- Namibia -- Economic models